Man Anxiety as Reflected in Ernest Hemingways The Old Man and the Sea - Dania Musoffa; Akhmad Multazim; Atikasari Husna; Lutfy F. Hudayah; Renovil Dramestika (Journal of Language and Literature, 2019)
In modern era, problems occur continuously and it triggers stress and anxiety. This study aims to describe characterization and the anxiety of the main character in The Old Man and The Sea, a novel by Ernest Hemingway. This studybelongs to library research that applied descriptive qualitative method with psychological approach. Reading and documentation techniques were used to collect the data. To analize the anxiety of the main character, a theory on psychological anxiety by Durand and Barlow were used. The result shows that: 1) the main character, Santiago, is described as a man who is kind, industrious, ambitious, powerful, smart, calm, cheerful, patient, confident and stubborn, 2) the anxieties felt by Santiago are Generalized Anxiety Disorder (GAD), Panic Disorder, Specific Phobia, Post-Traumatic Stress Disorder (PTSD) and Obsessive-Compulsive Disorder (OCD).